Analisis Faktor-faktor yang Memengaruhi Impulsive Buying pada Pengguna Shopee Live (Studi pada Generasi Z di Wilayah Jabodetabek) - Ni Luh Putu Dian Suyastrini; Erric Wijaya (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2026)
This study examines the influence of time pressure, price pressure, social influence, visuals, and sound on impulsive buying, mediated by arousal and pleasure. The research focuses on Generation Z (aged 13–28) in the Greater Jakarta area (Jabodetabek) who have purchased items via Shopee Live within the last three months. Data were collected through questionnaires and analyzed using the Partial Least Square (PLS) method with SmartPLS 4.0 software. The results indicate that price pressure and visuals significantly impact both arousal and pleasure. Conversely, time pressure and sound show no significant effect on either mediator, while social influence only significantly affects arousal. Mediation analysis reveals that price pressure, social influence, and visuals influence impulsive buying through arousal, while visuals and price pressure also influence it through pleasure. Ultimately, both arousal and pleasure serve as significant drivers of impulsive buying behavior among Generation Z on the Shopee Live platform.